Oncological Outcomes of Laparoscopic Nephroureterectomy Versus Open Radical Nephroureterectomy for Upper Tract Urothelial Carcinoma: An European Association of Urology Guidelines Systematic Review - Peyronnet, Benoit; Seisen, Thomas; Dominguez-Escrig, Jose-Luis; Bruins, Harman Max; Yuan, Cathy Yuhong; Lam, Thomas; Maclennan, Steven; N’dow, James; Babjuk, Marko; Comperat, Eva; Zigeuner, Richard; Sylvester, Richard J.; et al. (European urology focus, 2019)
Most series have suggested better perioperative outcomes of laparoscopic radical nephroureterectomy (RNU) over open RNU. However, the oncological safety of laparoscopic RNU remains controversial. To systematically review all relevant literature comparing oncological outcomes of open versus laparoscopic RNU. A systematic literature search using the Medline, Embase, and Cochrane databases and clinicaltrial.gov was performed in December 2014 and updated in August 2016. Randomised controlled trials (RCTs) and prospective or retrospective nonrandomised comparative studies comparing the oncological outcomes of any laparoscopic RNU with those of open RNU were included. The primary outcome was cancer-specific survival. The risk of bias (RoB) was assessed using Cochrane RoB tools. A narrative synthesis of the evidence is presented. Overall, 42 studies were included, which accounted for 7554 patients: 4925 in the open groups and 2629 in the laparoscopic groups. Most included studies were retrospective comparative series. Only one RCT was found. RoB and confounding were high in most studies. No study compared the oncological outcomes of robotic RNU with those of open RNU. Bladder cuff excision in laparoscopic groups was performed via an open approach in most studies, with only three studies reporting laparoscopic removal of the bladder cuff. Port-site metastasis rates ranged from 0% to 2.8%. No significant difference in oncological outcomes was reported in most series. However, three studies, including the only RCT, reported significantly poorer oncological outcomes in patients who underwent laparoscopic RNU, especially in the subgroups of patients with locally advanced (pT3/pT4) or high-grade upper tract urothelial carcinoma (UTUC), as well as in instances when the bladder cuff was excised laparoscopically. The current available evidence suggests that the oncological outcomes of laparoscopic RNU may be poorer than those of open RNU when bladder cuff is excised laparoscopically and in patients with locally advanced high-risk (pT3/pT4 and/or high-grade) UTUC. We reviewed the literature comparing the outcomes of two different surgical procedures for the treatment of upper tract urothelial carcinoma. Open radical nephroureterectomy is a surgical procedure in which the kidney is removed through a large incision in the abdomen, while in laparoscopic radical nephroureterectomy, the kidney is removed through a number of small incisions. Our findings suggest that the outcomes of laparoscopic radical nephroureterectomy may be poorer than those of open radical nephroureterectomy, particularly when the bladder cuff is also required to be removed. Laparoscopic radical nephroureterectomy may also be less effective in patients with locally advanced (pT3/pT4) or high-grade upper tract urothelial carcinomas. The oncological outcomes of laparoscopic radical nephroureterectomy may be poorer than those of open radical nephroureterectomy when bladder cuff is excised laparoscopically, and in patients with locally advanced high-risk (pT3/pT4 and/or high-grade) upper tract urothelial carcinoma.